2017
DOI: 10.1007/s11218-016-9365-7
|View full text |Cite
|
Sign up to set email alerts
|

Learning behaviour and learning outcomes: the roles for social influence and field of study

Abstract: Abstract:Research has demonstrated a significant role of discipline social identification in predicting learning approaches, even controlling for individual differences. Smyth, Mavor, Platow, Grace and Reynolds. (2015) suggest that learners share disciplinebased social identifications, and that this identification, in combination with relevant norms, influences the adoption of learning approaches. The current paper extends this analysis in two directions. First, the effect of broad field of study is examined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…Results from the correlation and regression analyses are all in line with previous literature (Bliuc et al, , ; Platow et al, ; Smyth et al, ; Smyth, Mavor, & Platow, ). As in these previous studies, there is a positive main effect association here between identification and the adoption of deeper learning approaches.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Results from the correlation and regression analyses are all in line with previous literature (Bliuc et al, , ; Platow et al, ; Smyth et al, ; Smyth, Mavor, & Platow, ). As in these previous studies, there is a positive main effect association here between identification and the adoption of deeper learning approaches.…”
Section: Discussionsupporting
confidence: 88%
“…These approaches have already been demonstrated to be subject to influence from strength of identification with a relevant social identity and from perceived study‐related norms associated with these identities (Bliuc et al, , ; Platow et al, ; Smyth et al, ). The current paper takes this body of research a step further, in line with the direction suggested more recently by Smyth and colleagues (Smyth, Mavor, & Platow, ), by examining learning approach intentions in a situation where multiple, potentially conflicting, intragroup normative influences are considered, particularly those drawn from the educator.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations